Determinants of Customer Loyalty in Mobile Telecommunication Industry in Bangladesh (Global Journal of Management and Business Research, 2017)
The objective of the study is to investigate the determinants of customer loyalty in telecom industry in Bangladesh The study surveyed 200 telecom customers in Bangladesh from Dhaka city to determine the key determinants that significantly influence customer loyalty Convenience sampling method was used to collect primary data Several hypotheses have been extracted from the conceptual framework and are tested using One-way ANOVA Multiple regression analysis Findings of study showed that service quality customer satisfaction trust corporate image have certain degree of relationship with customer loyalty but switching cost did not prove to have any significant relationship with customer loyalty It is also shown that service quality is the most dominant determinant among four 4 significant determinants which mostly lead customer to use a particular telecom operator s services repeatedly The findings suggest that telecom operators should put more emphasis on improving service quality customer satisfaction trust corporate image in order to increase loyalty among customers
Keywords: customer loyalty; service quality; customer satisfaction; trust; corporate image; switching cost